PERBANDINGAN MODEL PEMBELAJARAN PROCESS ORIENTED GUIDED INQUIRY LEARNING (POGIL) DAN GUIDED INQUIRY (GI) TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA - Widya Fitriani; Dedi Irwandi; Dewi Murniati (LPPM Universitas Negeri Jakarta, 2017)
This research was conducted because of the low critical thinking skills of students caused by the inappropriate use of learning models. POGIL and GI learning model is used as a learning model in accordance with the curriculum 2013. Where is aims to determine whether or not there is a difference application oflearning model Process Oriented Guided Inquiry Learning (POGIL) with Guided Inquiry (GI) learning model in students critical thinking skills on chemical equilibrium material. This research was conducted at SMAN 101 West Jakarta. The research method used in this research is experimental method, with research design the static group pretest-posttest design. The samples were taken by sampling purposive and divided into two experimental groups that is POGIL experimental group and GI experimental group. The technique of collecting data obtained through test instrument in essay form as many as 15 item which then analyzed by using t-test. The result of t-test is obtained by sig. 2-tailed = 0.000 and significant level (a) = 0.05. So that sig. 2-tailed smaller than significant (a) (0.000 <0.05) then Ho is rejected and Ha accepted. This shows that there are significant differences in the application of learning model Process Oriented Guided Inquiry Learning (POGIL) with learning model Guided Inquiry (GI) in students critical thinking skills. The results of this study can be used as a recommendation of innovative learning models in teaching and learning activities in the classroom. Keywords: Learning Model Process Oriented Guided Inquiry Learning (POGIL), Learning Model Guided Inquiry(GI), Critical Thinking Skills, Chemical Equilibrium Material